Influence of studying in higher educational establishment on students’ harmful computer habits - M.D. Kudryavtsev; I.E. Kramida; S.S. Iermakov (Physical Education of Students, 2016)
Purpose: to determine influence of educational process on prevalence of students’ harmful computer habits. Material: in the research 1st-3rd year students (803 boys and 596 girls) participated. All they specialized in discipline Physical culture. The students had no health disorders. Results: it was found that in average students have 2 computer habits everyone. The most probable and dangerous in respect to addicting are habits to use internet and computer games. Student, who has these habits, spends more than 4 hours a day for them. 33% of 1st year boys and 16% of 1st year girls spend more than 2 hours a day for computer games. 15-20 % of boys and 25-30% of year girls waste more than 4 hours a day in internet. 10-15% of boys spend more than 4 hours a day for computer games. It is very probable that these students already have computer games’ addiction. Conclusions: recent time dangerous tendency to watching anime has been appearing. Physical culture faculties and departments shall take additional measures on reduction of students’ computer addictions. Teachers of all disciplines shall organize educational process with the help of electronic resources so that not to provoke progressing of students’ computer habits.